2013
DOI: 10.1111/ijsw.12053
|View full text |Cite
|
Sign up to set email alerts
|

Are rural–urban migrants living in urban slums more vulnerable in terms of housing, health knowledge, smoking, mental health and general health?

Abstract: The magnitude of rural–urban migration in Bangladesh is increasing. Rapid urbanisation and a growing number of slums (dominated by migrants) pose many challenges to health. To our knowledge, studies regarding internal migration and health are scarce and results are mixed. Therefore, we compared several aspects, namely: housing, health knowledge, smoking, mental and general health, for three groups of migrants, designated urban natives/urban to urban migrants (UN/UU), rural to urban migrants (RU) and rural nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…This is due to several factors: those pertaining to the pulling of rural people to cities and push factors driving population away from rural areas. Often cited in the literature with respect to pull factors include the relative perception of better economic opportunities (e.g., Glaeser, 2011) and provision of basic services such as education and healthcare within cities (e.g., Khan, Kraemer, & Kraemer, 2014), or the freedom from restrictive social or cultural norms often found in rural areas (e.g., Opeyemi et al, 2012;Ullah, 2004). Push factors include rural poverty (e.g., Khan et al, 2014), excess agricultural labour supply (e.g., Oberai, 1993), environmental hardships (e.g., Ishtiaque & Mahmud, 2011), threat from natural disasters or conflict and war (e.g., Black, Bennett, Thomas, & Beddington, 2011).…”
Section: Rural-to-urban Migrationmentioning
confidence: 99%
“…This is due to several factors: those pertaining to the pulling of rural people to cities and push factors driving population away from rural areas. Often cited in the literature with respect to pull factors include the relative perception of better economic opportunities (e.g., Glaeser, 2011) and provision of basic services such as education and healthcare within cities (e.g., Khan, Kraemer, & Kraemer, 2014), or the freedom from restrictive social or cultural norms often found in rural areas (e.g., Opeyemi et al, 2012;Ullah, 2004). Push factors include rural poverty (e.g., Khan et al, 2014), excess agricultural labour supply (e.g., Oberai, 1993), environmental hardships (e.g., Ishtiaque & Mahmud, 2011), threat from natural disasters or conflict and war (e.g., Black, Bennett, Thomas, & Beddington, 2011).…”
Section: Rural-to-urban Migrationmentioning
confidence: 99%
“…Nevertheless, as previously reported (Egondi et al, 2013;Khan and Kraemer, 2014;Kruza et al, 2017;Yoda et al, 2017) human population is continuously being exposed to the risk of air pollution, for example, in 2014; about 92 percent of the world population was living in places where the WHO guidelines on air quality standards were not well met. The reports also, showed that around 88% of the premature deaths were registered in low-middleincome countries, mainly in the Western Pacific and South-east Asia due to air pollution.…”
Section: Introductionmentioning
confidence: 88%
“…The city's spatial expansion as well as the spread and growth of slum settlements in the city can largely be assigned to migration (Afsar, 2005;Islam, 2005;Siddiqui et al, 2010). Recent findings show that 88% of the people who are living in Dhaka's slums have moved to the city from rural areas (Khan & Kraemer, 2013). 2 Besides living in the city and using its basic services, rural-urban migrants contribute significantly to making the city work through their labour.…”
Section: The Imprints Of Rural-urban Migration In Dhakamentioning
confidence: 99%
“…The reflections and findings that are presented in this paper were enabled by him, as he initiated the project 'The Megaurban Food System of Dhaka, Bangladesh' (funded by the German Research Foundation, BO 680/35-1/-2). (Khan & Kraemer, 2013). (3) All the names of the involved persons have been anonymized in order to protect the interviewees.…”
Section: Acknowledgementsmentioning
confidence: 99%